Cofactor-mediated amyloidogenesis. Issue 3 (6th March 2019) - Madine, Jillian
Abstract : A recent study published in Bioscience Reports by Sheng et al. (Bioscience Reports, (2019)39, pii:BSR20182345] described a small but significant conformational change that occurs upon zinc binding and results in initiation of the amyloidogenic aggregation cascade of Golgi-Associated plant Pathogenesis Related protein 1 (GAPR-1) in the presence of heparin. The present study describes a two-stage process that is required for the initiation of the amyloidogenic aggregation cascade involving a concentration step and a conformation change to enhance accessibility of natively protected amyloidogenic regions for self-association. For GAPR-1 in the present study, these steps are provided by zinc binding causing the required conformational change enhancing accessibility of amyloidogenic regions, and heparin providing a template or scaffold in turn increasing the local protein concentration. Cofactors such as glycosaminoglycans and metal ions have been found associated with amyloid deposits in vivo and shown to affect protein assembly kinetics in vitro. Cofactor interactions with the amyloidogenic process are an area of great interest for therapeutic intervention for the wide range of diseases known to be associated with amyloid protein aggregation. The present study emphasises the need for enhanced structural understanding of cofactor–amyloid protein interactions and highlights that small subtle conformational changes can have large impacts on resulting aggregation processes.